2017
DOI: 10.1292/jvms.16-0614
|View full text |Cite
|
Sign up to set email alerts
|

Potential of electrolyzed water for disinfection of foot-and-mouth disease virus

Abstract: Acidic electrolyzed water (EW) (pH 2.6−5.8) and alkaline EW (pH 11.2−12.1) were examined as potential disinfectants against foot-and-mouth disease virus (FMDV). Using acidic EW with pH 2.6 and alkaline EW with pH >11.7, the viral titer decreased in vitro by > 4.0 log values, 2 min after the virus was mixed with EW at a 1:10 dilution. The strong virucidal effect of acidic EW (pH 2.6), but not that of alkaline EW (>11.7), seemed to depend on the chlorine level in the solution. Genetic analysis revealed that vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…An EW generator simultaneously produces a large amount of hypochlorous acid EW and strong alkaline water by electrolyzing water containing NaCl or KCl in an electrolysis chamber. Acidic EW has a virucidal effect against human immunodeficiency virus, hepatitis B virus, herpes simplex viruses, norovirus, influenza A virus, and food-and-mouth disease virus [ [7] , [8] , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…An EW generator simultaneously produces a large amount of hypochlorous acid EW and strong alkaline water by electrolyzing water containing NaCl or KCl in an electrolysis chamber. Acidic EW has a virucidal effect against human immunodeficiency virus, hepatitis B virus, herpes simplex viruses, norovirus, influenza A virus, and food-and-mouth disease virus [ [7] , [8] , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the proponents of water ionisers, acidic water produced in these devices is a natural bactericide and pesticide (Bui et al, 2017;Sun, Zhang, Chen, & Han, 2012;Abbasi & Lazarovits, 2006). They also claim that alkaline water is better in neutralising stomach gastric acid, detoxifies the organism, and acts like a natural antioxidant and alkalizing substance due to a large content of oxygen and negative oxidation-reduction potential (Mousa, 2016;Laucevičius, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The predominant active oxidizing agent in AEW at pH 5.0-6.8 is considered to be HOCl. Several previous studies investigating the general efficacy of HOCl reported its favorable antimicrobial effects against a wide range of bacteria, fungi, and viruses, including foot-and-mouth disease virus, and AIV [4,9,10,15,25,26,29,30,31]. To our knowledge, this is the first study to investigate the virucidal effect of AEW on ASFV.…”
Section: Discussionmentioning
confidence: 81%
“…Chlorine-based disinfectants, such as sodium hypochlorite, are widely used owing to their high efficacy and low cost. As a disinfectant, chlorine is a strong oxidant and is used to control against a broad spectrum of bacteria and viruses in the clinical, agricultural, and food industries [4,11,25,27,28,29]. However, a common concern is that it is potentially toxic, corrosive, and volatile and leaves toxic residues [1,10,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation